2007
DOI: 10.1086/520620
|View full text |Cite
|
Sign up to set email alerts
|

21 cm Synthesis Observations of VIRGOHI 21—A Possible Dark Galaxy in the Virgo Cluster

Abstract: Many observations indicate that dark matter dominates the extragalactic universe, yet no totally dark structure of galactic proportions has ever been convincingly identified. Previously, we have suggested that VIRGOHI 21, a 21 cm source we found in the Virgo Cluster using Jodrell Bank, was a possible dark galaxy because of its broad line width ($200 km s À1 ) unaccompanied by any visible gravitational source to account for it. We have now imaged VIRGOHI 21 in the neutral hydrogen line and find what could be a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 41 publications
2
53
0
Order By: Relevance
“…The dark galaxy VIRGOHI 21 was observed in the Virgo Cluster to have a similar H I tail; it is a starless H I cloud, apparently connected by a faint H I bridge to NGC 4254, a spiral galaxy located ∼20 arcmin away (Minchin et al 2007). Later numerical simulations by Duc & Bournaud (2008) showed that the long tail of the cloud may have resulted from a high-velocity collision, probably with the parent galaxy NGC 4254.…”
Section: Ngc 4424mentioning
confidence: 99%
“…The dark galaxy VIRGOHI 21 was observed in the Virgo Cluster to have a similar H I tail; it is a starless H I cloud, apparently connected by a faint H I bridge to NGC 4254, a spiral galaxy located ∼20 arcmin away (Minchin et al 2007). Later numerical simulations by Duc & Bournaud (2008) showed that the long tail of the cloud may have resulted from a high-velocity collision, probably with the parent galaxy NGC 4254.…”
Section: Ngc 4424mentioning
confidence: 99%
“…Potential detections, such as HIPASS J0731−69 (Ryder et al 2001), are more likely to be the result of tidal or rampressure stripping, in particular as they tend to occur near luminous galaxies with obvious signs of recent interaction. More recently, several 'dark galaxy' candidates have been reported (e.g., Minchin et al 2007;Oosterloo et al 2013), in particular as part of the ALFALFA survey Haynes et al 2011;Janowiecki et al 2015). While the nature of some of these objects is still uncertain, many other 'dark galaxy' candidates have since either been identified as tidal debris Duc & Bournaud 2008;Cannon et al 2015;Taylor et al 2017), or faint stellar counterparts have been detected in deep optical data .…”
Section: Lack Of Extragalactic H I Gasmentioning
confidence: 99%
“…According to a more exotic scenario, star-less intergalactic HI clouds might reveal the presence of so-called "dark galaxies", i.e. galaxies embedded in a massive dark matter halo that would contain very few baryons, only in the form of gas (see the proceedings of IAU symposium 244 dedicated to dark galaxies and Minchin et al, 2007). An example of such objects is VirgoHI21, near the spiral NGC 4254 shown on Figure 8 (bottom panel).…”
Section: When Components Are Missing: Hi Without Optical Counterpartsmentioning
confidence: 99%